Social Security Fund Usage and Perception of Elderly People - Kharal, Hemchandra; Adhikari, Loknath; Kunwar, Dhan Kumar (International Research Journal of Parroha, 2024)
This study investigates the usage, perception, and experiences of elderly individuals regarding the Social Security Fund (SSF) in Nepal. The primary objectives are to identify how the elderly utilize the SSF, understand their perceptions of the fund, and document their experiences. A mixed-methods approach was employed, combining quantitative surveys and qualitative interviews to provide a comprehensive overview of the SSF's impact on the elderly population in Sainamaina Municipality, Rupandehi District, Nepal. Data were collected from respondents across all 11 wards of the municipality. The findings reveal that perceptions of the SSF among elderly individuals are influenced by personal experiences and economic circumstances. Those receiving regular benefits view the SSF as a vital source of financial stability, primarily using it for essential needs such as food, healthcare, and clothing. However, many beneficiaries consider the benefits insufficient to cover living costs and express concerns about the long-term sustainability of the SSF due to potential policy changes and funding cuts.